On the Issue of Obligatory Hazard Activity Liability Insurance of Lifts Operation in Apartment Houses - D. A. Storozhuk (Сибирское юридическое обозрение, 2013)
The article deals with the problems of legislation application of Obligatory Hazard Activity Liability Insurance, civic responsibility of the owner of the dangerous object for doing harm as a result of damage caused by lift operation in apartment houses.